The impact of mental and psychological state on metatarsophalangeal joint replacement outcomes in patients with freiberg’s infraction - Jianmin Qu; Gang Wang; Shihang Cao; Xiaocong Liu; Yi Li; Jun Lu; Junkui Xu (Journal of Orthopaedic Surgery and Research)
Abstract Purpose To investigate the impact of preoperative psychological factors on outcomes following metatarsophalangeal joint replacement surgery in patients with Freiberg’s infraction. Methods This retrospective study included 127 patients diagnosed with Freiberg’s infraction who underwent metatarsophalangeal joint replacement surgery at Xi’an Honghui Hospital’s Department of Foot and Ankle Surgery between August 2013 and September 2023. Patients were stratified into two groups based on preoperative psychological status: Group A comprised patients with preoperative anxiety and/or depression symptoms, while Group B included patients without such symptoms. The Hospital Anxiety and Depression Scale (HADS) and visual analogue scale (VAS) were administered preoperatively and at final follow-up to assess psychological status and pain levels. Primary outcome measures included the 0–100 mm VAS for pain and the American Orthopaedic Foot and Ankle Society (AOFAS) functional score. Results Of 127 patients, 91 (71.7%) completed follow-up. Among these 91 patients, 53 (58.2%) had preoperative anxiety and/or depression symptoms. Both groups demonstrated significant improvements in all measured parameters compared to preoperative values. However, Group A showed significantly worse clinical outcomes than Group B across all assessment measures. Conclusion Metatarsophalangeal joint replacement surgery significantly improves pain and functional outcomes in patients with Freiberg’s infraction. However, preoperative anxiety and depression are associated with inferior postoperative outcomes.